Suggested Improvements of Instagram Brand Communication for Czech Airlines - Bártová, Tereza (2022)
During times when the only way advertisements could have been spread just by the word of mouth, there was nothing much to discuss about the right choice of communication style. When newspapers and street banners occurred, things got more difficult, but it is nothing compared to today’s world that got enlarged by social media. They changed the whole paradigm of the traditional marketing communication and those who cannot keep up with new trends in the virtual world arising every day, cannot breakthrough the market, whatever industry they operate in. The main purpose of this bachelor thesis is a comparison of communication strategies and brand representation on Instagram of Turkish Airlines, Emirates and British Airways with the company Czech Airlines. An analysis of their PR activities on the platform towards the wide public is used to reveal weaknesses in communication strategy of Czech Airlines on Instagram, and, based on findings, suggest appropriate improvements of their approach towards their presence on social media.